A novel analysis of two parallel connected inverters for isolated DC microgrid system by using droop controller technology - J. Venumadhav; Durgam Rajababu; CH Hussain Bhasha (Results in Engineering)
This paper examines the voltage and current (V-I) stability and harmonic reduction in a decentralized DC microgrid with two parallel-connected inverters under unbalanced load conditions. However, oscillations were observed in systems with parallel converters by connecting them with non-linear loads and by operating with unbalanced loads. The system incorporates current and voltage controllers, a droop controller for reactive power (VAR), and active or real power (KW) sharing. Stability is improved when comparing isolated or grid-connected systems to voltage-current (VI) droop control, which acts as a resistor, and conventional droop control methods that depend on the relationships between reactive power (VAR) and voltage (V), real power (KW), and frequency (Hz), and by using voltage-current droops when droop coefficients have low values. The harmonics in parallel inverters are reduced by incorporating proper PI controllers in LCL filters and by choosing proper droop coefficients. The study develops different control strategies to reduce oscillations in voltage and current output waveforms and reduce THD’s to 1 to 8 % in a two-parallel connected voltage source inverter Simulink model of the system, based on the conversion of three-phase time-variant quantities to two-phase time-variant quantities. This model integrates an LCL filter, a droop controller, a voltage controller, and a current controller. MATLAB/Sim Power Systems is used for developing the proposed system.